Analisis Media Promosi Pariwisata (Studi pada Wisata Permandian Paisu Matube) - Ramansyah; Yusuf, Multia; Rumambie, Wira Pratama (Jambura Jurnal Ilmu Komunikasi, 2025)
This research aims to analyze the promotional media strategies used in the management of the Paisu Matube hot springs tourism site in Banggai Laut Regency. This tourist attraction has appealing natural potential; however, the low number of domestic visitors indicates that the promotion being carried out is not optimal. This study employs a qualitative approach by examining the roles of the Tourism Office and the Community Awareness Group (Pokdarwis) in utilizing various promotional media, including social media, print media, and electronic media. The results indicate that tourism promotion is predominantly conducted through social media platforms such as Facebook, while print and electronic media are not utilized to their full potential. Therefore, there is a need for the development of more diverse and intensive promotional strategies to increase the interest of local and international tourists. This research contributes theoretically to the field of communication as a tool for tourism promotion and provides practical benefits for tourism managers in optimizing promotional media to boost visitor numbers.